The Association of a Preschool Voice Education Program with Changes in Yelling Frequency - Marcus, Lauren; Kiernan, Barbara; Barkmeier-Kraemer, Julie M. (Seminars in Speech and Language, 2013)
Voice problems in children can occur as early as infancy. Early onset of voice problems can carry social and academic penalties, and negatively affect voice in adolescence or adulthood. Unfortunately, only 1% of school-aged children receive voice therapy despite a 6 to 24% prevalence of voice disorders in school-aged children. One alternative may be to use a classroom-based voice education curriculum to effectively reduce yelling frequency, the most common behavior associated with phonotrauma-related voice problems in children. A classroom-based voice education curriculum was administered to preschool children by the preschool speech-language pathologists in a university-affiliated program. Classroom teachers provided cueing and reinforcement of curriculum strategies for 8 weeks following the program. Baseline frequencies of participant yelling behaviors were compared with postprogram frequencies. Results demonstrated significant reduction in yelling frequencies from pre- to postprogram, particularly in those judged as high-frequency yellers prior to the program. Important factors for future consideration are discussed.
Keywords: Pediatric; voice; education; prevention; preschool